Research Status of Synthetic Oil Well Cement Retarder - Zihan, Guo; Ziyang, Liu; Kai, Liao; Xianghui, Yang (Recent Patents on Engineering, 2021)
Background: Oil well cement retarder is an additive that can extend time for thickening cement slurry, which can ensure the safety of cement. At present, the oil well cement retarder is mainly composed of synthetic materials, which are mainly divided into three major categories: compound polymer, AMPS polymer and non-AMPS. Methods: In this paper, the research status of synthetic oil well cement retarder in recent years is reviewed, and its shortcomings and development trends are analyzed. It is pointed out that the shortage of synthetic retarder mainly lies in problems, including large temperature sensitivity, small temperature application range, abnormal thickening curve, great influence on high temperature settlement stability and cement stone strength development. Conclusion: The development direction of oil well cement retarder is mainly focused on developing intelligent retarder and degradable retarder to meet the cementing needs of oilfields and ensure cementing effect increasing steadily.
Keywords: compound polymer